Structural Brain Changes following Long-Term 6° Head-Down Tilt Bed Rest as an Analog for Spaceflight - Roberts, D.R.; Zhu, X.; Tabesh, A.; Duffy, E.W.; Ramsey, D.A.; Brown, T.R. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Following long-term spaceflight, a subset of the National Aeronautics and Space Administration astronauts present with visual impairment and increased intracranial pressure, known as visual impairment and intracranial pressure syndrome. We investigated structural brain changes following long-term head-down tilt bed rest as a spaceflight analog.MATERIALS AND METHODS: Volumetric analysis was performed on structural pre- and post–bed rest brain MR images.RESULTS: Comparing post–bed rest to pre–bed rest images, we found the following: 1) no significant group differences in GM, WM, CSF, or ventricular volumes; 2) shift of the center of mass of the brain upward and posterior rotation of the brain relative to the skull; 3) a significant correlation between posterior brain rotation and changes in ventricular volume; and 4) significant increases in brain tissue density in regions at the vertex, including the frontoparietal lobes, with contraction of adjacent extra-axial CSF spaces, and significant decreases in tissue density in areas along the base of the brain, including the orbitofrontal cortex.CONCLUSIONS: We observed widespread morphologic changes with brain tissue redistribution in response to gravity changes; possible associated functional changes are unknown. The observation that ventricular change is correlated to posterior brain rotation suggests an alteration in CSF homeostasis. Ultimately, to elucidate any structural changes that may play a role in visual impairment and intracranial pressure syndrome, volumetric analysis of pre- and postflight structural scans of astronauts is needed.BRbed restICVintracranial volumeIIHidiopathic intracranial hypertensionNASANational Aeronautics and Space AdministrationVIIPvisual impairment and intracranial pressure